Microcalcification detection with and without CAD system (LIBCAD): A comparative study - Abdel Razek, Naglaa M.; Yousef, Waleed A.; Mustafa, Waleed A. (Egyptian journal of radiology and nuclear medicine, 2013)
The objective of this research is to assess the performance of the LIBCAD as a recent prototype CAD in microcalcification detection, and compare it to the readings of an experienced radiologist. We used 100 normal cases (437 images) to calculate the False Positive (FP) results and 488 cases (1952 images) with abnormalities. All the images are digital mammography. Out of these 488 cases, only 38 cases (67 images) have malignant microcalcifications. Those 38 cases are used to calculate the True Positive findings (sensitivity). Malignant microcalcifications were detected by the radiologist in 100% (38/38) of cases: 86.8% (33/38) microcalcifications alone and 13.2% (5/38) microcalcifications with masses. The performance was tested at two threshold levels. At a threshold of 4 foci per cluster (an aggressive threshold) malignant microcalcifications were detected in 97.4% (37/38) of cases: 86.8% (33/38) microcalcifications alone and 10.5% (4/38) microcalcifications with masses. At a threshold of 8 foci per cluster (a less aggressive threshold) the detection rate was 92.1% (35/38) of cases: 84.2% (32/38) microcalcifications alone, and 7.9% (3/38) microcalcifications with masses.